Study on probability or number theory - Zhuang, Yugui (Nanyang Technological University, 2023)
This report is primarily intended for the study of probability and number theory. By studying some real-life cases, to find some excellent strategies to maximize the benefits. Through a given scenario, use probability knowledge to analyze and improve, and obtain corresponding results. Then through programming to simulate the scenes in life, and finally through a large numbers of simulation results in the program, the results are relatively close to the theoretical value. Probability and number theory are very important topics for computer technology. The role of probability theory and mathematical statistics permeates all aspects, from deviation and variance analysis to better fit to calculation of probability to achieve prediction, from random initialization to speed up training to regularization and normalized data processing to avoid over-fitting. Probability provides randomness for artificial intelligence and provides a basis for prediction, while statistics process and analyze data to make the results better to meet our requirements, more universal and general, so that in our application.